O setor público e o desenvolvimento humano dos municípios brasileiros: uma análise a partir do censo 2010 - Nobre, José Eduardo Silva (2021)
The main objective of this dissertation is to verify the influence of the public sector on human development of Brazilian municipalities. The results showed that government spending, reflected in the Public Gross Value Added (public GVA), is very important for the Municipal Human Development Index (MHDI) throughout the country, from the poorest municipalities to the richest. The econometric model showed that each increase of one percent in the public GVA implies an increase of 0.0157 in the MHDI and that each increase of one percent in the GVA of services implies an increase of 0.0710 in the MHDI. Considering the strong correlation between public GVA and service GVA and the very strong influence of service GVA on the MHDI, an additional model was used in which the service GVA is explained by the public GVA. Its result was significant, showing that each increase of one percent in public GVA implies an increase of 1.34% in service GVA.